2007
DOI: 10.1029/2006gl027927
|View full text |Cite
|
Sign up to set email alerts
|

Implications of temporal change in urban heat island intensity observed at Beijing and Wuhan stations

Abstract: Temporal change in urbanization‐induced warming at two national basic meteorological stations of China and its contribution to the overall warming are analyzed. Annual and seasonal mean surface air temperature for time periods of 1961∼2000 and 1981∼2000 at the two stations of Beijing and Wuhan Cities and their nearby rural stations all significantly increase. Annual and seasonal urbanization‐induced warming for the two periods at Beijing and Wuhan stations is also generally significant, with the annual urban w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
131
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(148 citation statements)
references
References 9 publications
12
131
0
5
Order By: Relevance
“…Beijing is characterized by a warm temperature zone and has a typical continental monsoon climate with four distinct seasons. Rapid urbanization and city expansion started in the late 1980s, resulting in significant UHI effects [38,39]. Previous studies have found that the mean daily temperature in urban areas is 4.6 higher than the mean daily temperature in the suburbs [40].…”
Section: Study Areamentioning
confidence: 99%
“…Beijing is characterized by a warm temperature zone and has a typical continental monsoon climate with four distinct seasons. Rapid urbanization and city expansion started in the late 1980s, resulting in significant UHI effects [38,39]. Previous studies have found that the mean daily temperature in urban areas is 4.6 higher than the mean daily temperature in the suburbs [40].…”
Section: Study Areamentioning
confidence: 99%
“…The key of this method depends on whether or not those sites or stations can be objectively classified. In general, such a classification utilizes either population data [6][7][8][9][10][11][12][13][14][15][16][17] or satellite data (such as nighttime light imagery and land cover dataset) [18][19][20][21][22][23] as well as the geographic location of the stations. In addition, Empirical Orthogonal Function (EOF) [24,25], Principal Component Analysis (PCA) [26,27] and station metadata [28] can also be applied to define reference or rural stations.…”
Section: Citationmentioning
confidence: 99%
“…Some previous studies indicated that urbanization has little impact on regional warming [7,13,26,27]. However, recent investigations have suggested that the urbanization process can not only increase the local daily temperature, but also play an essential role in regional climate change [6,9,12,[14][15][16][17][20][21][22][23][24][28][29][30]35,36]. Using the OMR method, Zhou et al [29] and Zhang et al [30] found that the urbanization exerts a significant influence on temperature trends in eastern China.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the small population of the residential areas near stations and the similar physiographic characteristics to the target station, the reference stations are also required to have the continuous observation records with as possible as less the missing observational values. The two weather stations were ever used as reference stations in previous studies of urbanization effect on the SAT trends of Beijing station Ren et al 2007). …”
Section: Methodsmentioning
confidence: 99%